Ethane-1,2-diaminium 4,4′-sulfonyldibenzoate - Smith, Graham (International Union of Crystallography, 2011)
In the title salt, C(2)H(10)N(2) (2+)·C(14)H(8)O(6)S(2−), both the ethylenediaminium cations and the 4,4′-sulfonyldibenzoate dianions have crystallographic twofold rotational symmetry. They are interlinked by aminium N—H⋯O(carboxylate) hydrogen-bonding associations, giving sheets parallel to (101) and are further linked along [010], forming a three-dimensional structure.